2013
DOI: 10.1016/j.livsci.2012.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters for test-day milk yield, 305-day milk yield, and lactation length in Guzerat cows

Abstract: a b s t r a c tMilk production in tropical environments requires the use of crossbreeding systems including breeds well adapted to harsh conditions, but with lower productivities when compared to specialized breeds. Besides the genetic improvement for milk production, lactation lengths also need to be studied for most of these breeds. Accordingly, genetic parameters were estimated for 305-day cumulative milk yield (MY305), test-day milk yield (TDMY), and lactation length (LL) using information from the first l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
6
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 20 publications
7
6
3
Order By: Relevance
“…The heritability estimates obtained by the TDMO ranged from 0.15 (first month) to 0.27 (third month), and the estimates in the initial lactation phase were lower than those obtained by the RRMs. These heritability estimates are similar to those obtained by Santos et al (2013b) for the Guzerat breed, and by Ledic et al 2002 for the Gyr breed, which ranged from 0.16 to 0.24 and from 0.14 to 0.24, respectively. However, Herrera et al (2008) found the highest heritability estimates, from 0.14 to 0.34 for Gyr breed, while Bignardi et al (2008) found the lower estimates, which ranged from 0.07 to 0.19 for the Holstein breed.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The heritability estimates obtained by the TDMO ranged from 0.15 (first month) to 0.27 (third month), and the estimates in the initial lactation phase were lower than those obtained by the RRMs. These heritability estimates are similar to those obtained by Santos et al (2013b) for the Guzerat breed, and by Ledic et al 2002 for the Gyr breed, which ranged from 0.16 to 0.24 and from 0.14 to 0.24, respectively. However, Herrera et al (2008) found the highest heritability estimates, from 0.14 to 0.34 for Gyr breed, while Bignardi et al (2008) found the lower estimates, which ranged from 0.07 to 0.19 for the Holstein breed.…”
Section: Resultssupporting
confidence: 90%
“…For Guzerat breed, Santos et al (2013a) found -0.15 and -0.03 for genetic correlation between records at the beginning and at the end of lactation, with Wilmink and Ali & Schaeffer function respectively. However, Santos et al (2013b), using a multi-trait model, estimated values which ranged from 0.91 to 0.56 between all monthly milk yields.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The estimates for LMY and 305LMY were higher compared with previous studies of improved zebu in low-input production systems in sub-Saharan Africa (Ilatsia et al, 2007;Badri et al, 2011). Conversely, the repeatability estimates for LL was moderate, but consistent with other studies of improved zebu in the tropics (Ilatsia et al, 2007;Badri et al, 2011;Santos et al, 2013). The repeatability estimates for production traits indicate that selection of the best cows to be kept in the herd for production could be done with some degree of precision based on estimates for LMY, 305LMY and LL of the cows.…”
Section: Figuresupporting
confidence: 85%
“…Strategies for crossbreeding Bos taurus taurus with Bos taurus indicus are important in Brazil to achieve the balance between yield and adaptability of animals to adverse conditions in the country (Santos et al 2013) and explore the benefits of heterosis and complementarity originated from the crossbreeding between different breeds (Canaza-Cayo et al 2014).…”
Section: Introductionmentioning
confidence: 99%